Large facial congenital melanocytic nevus: a case report - Sharma, Deepti; Sharma, Chandra Madhur (International Journal of Research in Medical Sciences, 2017)
Congenital nevi are hyperpigmented macular lesions that are derivatives of the melanoblasts. Crude incidence estimates suggest that approximately 1 in 20 000 are born with a large CMN and 1 in 500 000 are born with a very large (giant) CMN. They occur in less than 1% of the neonates in any site of the body. The giant congenital nevus is greater than 20 cm in size, pigmented and often hairy. We report a classical case of large congenital melanocytic nevus present over face. The case report is being presented because of its rarity.